The Nature and Emergence of the Língua Geral Amazônica according to Mufwene’s Language Ecology Model - Finbow, Thomas (Revista do GEL, 2023)
This paper addresses two aspects of the Língua Geral Amazônica (LGA). First, we propose that Língua Geral as a technical term in Portuguese was inspired by administrative practices in Spain’s American colonies and that, given contemporary usage, the term should be understood functionally as any Tupi-Guarani variety broadly mutually comprehensible with the colonial Old Tupi, rather than as a structurally modified variety or the speech of a particular ethnic or social group, as has been claimed. We then briefly analyse two recent hypotheses that treat the emergence of LGA as creolisation (VIEIRA; ZANOLI; MÓDOLO, 2019; NOBRE, 2019). Next, we apply key notions of the Language Ecology creolisation model (MUFWENE, 2003, 2008) to the formation of LGA and suggest a periodization.